Antibiotic-Induced Pathobiont Dissemination Accelerates Mortality in Severe Experimental Pancreatitis - Soares, Fernanda S.; Amaral, Flávia C.; Silva, Natália L. C.; Valente, Matheus R.; Santos, Lorena K. R.; Yamashiro, Lívia H.; Scheffer, Mara C.; Castanheira, Fernanda V. E. S.; Ferreira, Raphael G.; Gehrke, Laura; Alves-Filho, José C.; Silva, Luciano P.; et al. (Frontiers in Immunology, 2017)
Although antibiotic-induced dysbiosis has been demonstrated to exacerbate intestinal inflammation, it has been suggested that antibiotic prophylaxis may be beneficial in certain clinical conditions such as acute pancreatitis (AP). However, whether broad-spectrum antibiotics, such as meropenem, influence the dissemination of multidrug-resistant (MDR) bacteria during severe AP has not been addressed. In the currently study, a mouse model of obstructive severe AP was employed to investigate the effects of pretreatment with meropenem on bacteria spreading and disease outcome. As expected, animals subjected to biliopancreatic duct obstruction developed severe AP. Surprisingly, pretreatment with meropenem accelerated the mortality of AP mice (survival median of 2 days) when compared to saline-pretreated AP mice (survival median of 7 days). Early mortality was associated with the translocation of MDR strains, mainly Enterococcus gallinarum into the blood stream. Induction of AP in mice with guts that were enriched with E. gallinarum recapitulated the increased mortality rate observed in the meropenem-pretreated AP mice. Furthermore, naïve mice challenged with a mouse or a clinical strain of E. gallinarum succumbed to infection through a mechanism involving Toll-like receptor-2. These results confirm that broad-spectrum antibiotics may lead to indirect detrimental effects during inflammatory disease and reveal an intestinal pathobiont that is associated with the meropenem pretreatment during obstructive AP in mice.